Climate change and health : an analysis of causal relations on the spread of vector-borne diseases in Brazil - Walter Leal Filho and Juliane Bönecke and Hannah Spielmann and Ulisses M. Azeiteiro and Fatima Alves and Mauren Lopes de Carvalho and Gustavo J. Nagy (Journal of Cleaner Production, 2018)
The increases in greenhouse gas concentrations caused by anthropogenic activities such as industrial emissions, transport and burning of forests and other resources, recorded over the past decades, are known to have an impact on the global environment. In particular, this paper reviews the evidence that climate change has an impact on human health as a whole and on the spread of vector-borne diseases in particular. It offers an analysis of previous research on the connections between climate change and health, with a case study from Brazil, and lists some areas which may guide future policy-making.
Keywords: Health; Extreme events; Arbovirus infections; Brazil; Zika; Policy-making